Morphophysiology of the passion fruit ‘BRS Rubi do Cerrado’ irrigated with saline waters and nitrogen fertilization - Maria de Sousa Silva Neta, Alzira; Lauriane Almeida dos Anjos Soares,; Geovani Soares de Lima,; Luderlandio de Andrade Silva,; Fagner Nogueira Ferreira,; Pedro Dantas Fernandes, (Comunicata Scientiae, 2020)
This study aimed to evaluate the gas exchanges and growth of the purple passion fruit cultivar ‘BRS Rubi do Cerrado’ as a function of the salinity levels of the irrigation water and nitrogen fertilization. The research was conducted in pots adapted as drainage lysimeters, placed within a plant nursery, using a Regolithic Neosol of sandy texture, in the municipality of Pombal-PB, Brazil. A randomized block design was used, testing five levels of electrical conductivity of irrigation water (0.3, 1.1, 1.9, 2.7, and 3.5 dS m-1) associated with four doses of nitrogen (50, 75, 100, and 125% of the recommendation). The irrigation water salinity above 0.3 dS m-1 compromised the leaf area and the relative water content of the purple passion fruit ‘BRS Rubi do Cerrado’. High doses of nitrogen enhance the deleterious effects of irrigation water salinity on stomatal conductance, transpiration, internal CO2 concentration, CO2 assimilation rate, number of leaves, stem diameter, and height of purple passion fruit plants. When waters with salinity levels of up to 1.3 dS m-1 are used, the dose of 125 mg of N kg-1 of soil is recommendation for providing increases in the CO2 assimilation rate of the purple passion fruit ‘BRS Rubi do Cerrado’ at 70 days after sowing (DAS). Water salinity increases electrolyte leakage, regardless of nitrogen doses.